SOURCE BASIS OF THE WORK “AL-KAMIL FIT-TARIKH” - Agzamova Muhabbatxon Mirtoxirovna (Galaxy International Interdisciplinary Research Journal, 2024)
The work of one of the medieval historians Abu Hasan Izzuddin Ali ibn Muhammad Jazari “Al-Kamil fit-tarih” is recognized as the most reliable source in modern research. This article explains the original meaning of the word "Al-Kamil fit-tarikh". Also, it reveals the place of the word “Tarikh ar-rusul val-muluk”, which is considered important when writing a work. In particular, Ibn Asir made up historical processes up to 302/915 based on the work of Muhammad ibn Jarir Tabari “Tarikh ar-rusul val-muluk” and events after 628/1230 based on various scattered sources and wrote a beautiful historical work, scientifically analyzed.